2016
DOI: 10.1002/lary.26027
|View full text |Cite
|
Sign up to set email alerts
|

Are industry financial ties associated with greater scholarly impact among academic otolaryngologists?

Abstract: NA Laryngoscope, 127:87-94, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…During recent years, the h index has been proposed as a better measure of scholarly influence compared with the number of publications and total number of citations. 5,8 Svider et al 9 found that academic otolaryngologists receiving more than $1000 in industrial contributions have higher h indices compared with otolaryngologists receiving less than $1000 (h index, 17.8 vs 10.9; P < .001). They also found that mean payments and the proportion of academic otolaryngologists receiving more than $1000 in payments significantly increased with higher academic rank (P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, the h index has been proposed as a better measure of scholarly influence compared with the number of publications and total number of citations. 5,8 Svider et al 9 found that academic otolaryngologists receiving more than $1000 in industrial contributions have higher h indices compared with otolaryngologists receiving less than $1000 (h index, 17.8 vs 10.9; P < .001). They also found that mean payments and the proportion of academic otolaryngologists receiving more than $1000 in payments significantly increased with higher academic rank (P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent look at such relationships among otolaryngologists noted that the field generally has modest industry relationships compared with physicians in other surgical specialties . Another recent analysis noted that significant industry relationships (ie, receiving >$1,000) had an association with greater scholarly impact among academic otolaryngologists …”
Section: Discussionmentioning
confidence: 99%
“…The CMS Open Payment website (https://www.cms.gov/openpayments/) was accessed to determine the extent of industry relationships with these providers during 2014. This website was created by the PPSA, a part of the Affordable Care Act, in an attempt to provide transparency regarding industry‐physician relationships, and has been used in numerous analyses exploring industry relationships among physicians . The CMS website categorizes industry payments into various categories, including research payments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations